Trade Union Relationship with Corporate Management - Tini Mogea (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
The need to manage a good and coordinated relationship among employees is critical in human resource management. In order to achieve organizational goals, the relationships between individuals involved in the context must be well managed, especially if the context is broader and involves a union. This brief article will focus on the relationship within the union. The fundamental question here is,